Oral Manifestation of Papillon-Lefevre in Two Siblings - Nydia Hanan; Satiti Kuntari; Els Sunarsih Budipramana (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2023)
Background: Papillon-Lefèvre Syndrome (PLS) is a very rare genetic disorder (autosomal recessive) that usually affects infants between the ages of one and five years. PLS is characterized by palmar-plantar hyperkeratosis and premature loss of primary and permanent teeth with extensive, severe, and rapid destruction of the alveolar bone, leading to the premature loss of both teeth. Objective: To report on the management of PLS patients. Case: A 9-year-old girl and a 2.5-year-old boy from Nganjukto General Hospital, Pediatric Dentistry Division, RSGM Airlangga University with the main complaints of upper left tooth pain, rocking, difficulty eating, erythematous hyperkeratosis hands and feet, periodontal inflammation, mobility. bad teeth. Case Management: Nine-year-old girl: Teeth #26 and #46 could not be retained and extracted due to buccoversion and severe mobility. Periodontal supportive therapy was periodontal debridement, scaling and root planing and oral hygiene counseling with 0.20% chlorhexidine gluconate. Two-and-a-half-year-old boy: Too young, he is observed every 3 months. It is recommended to take vitamin B complex in appropriate doses and fruit juice as an additional supplement. Conclusion: Intensive periodontal treatment and administration of antibiotics only delays the progression of periodontal disease and cannot be used to prevent primary and permanent teeth. Extensive and repeated prosthodontic treatment is required to provide functional teeth to children during their period of jaw growth.